The utility of crab shell powder in the treatment of rickets - Ri Gon; Mi-Ra Pak; Ok-Son Ri; Hyok Kim (Wolters Kluwer Medknow Publications, 2020)
Purpose: To estimate the effect of treatment for rickets by crab shell powder (CSP). Objects and Methods: We supplied children with rickets with calcium lactate and CSP and observed the serum concentrations of calcium, phosphorus, alkaline phosphatase (ALP) in preadministration and postadministration. Results: Postadministration serum concentrations of calcium, phosphorus, and ALP increased significantly compared to preadministration in both groups (P < 0.05), but significance between two groups is not recognized. Conclusion: The effective ratio of calcium lactate and CSP in the treatment for rickets has no difference, but CSP markedly decreased the incidence of concomitant disorders compared with calcium lactate.